PENGARUH BAURAN PROMOSI YANG DILAKSANAKAN OLEH KFC MAKASSAR TERHADAP KEEFEKTIFAN KINERJA PERUSAHAAN - Ansir Launtu (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aims to determine the application of the promotional mix used by Restaurant Kentucky Fried Chicken (KFC) Makassar. This study descriptive qualitative research that will provide an overview the implementation of the promotion mix conducted Restaurant Kentucky Fried Chicken (KFC) Makassar in increasing the amount of buyer. Implementation activities Makassar KFC promotion mix is done by advertising, namely the promotion of the use of multiple media, such as newspapers, radio, installation of signs (nameplate), banners and brochures. Then the individual sales (face to face), namely through the promotion of energy waitresses and distribute flyers. Furthermore, sales promotion, namely promotion by way of trade promotion activities, promotion package, sponsorship and exhibition that followed. While the publication is in cooperation with the press on events and the opening of a new office inauguration Restaurant Kentucky Fried Chicken (KFC) Makassar. KFC promotion activities carried on successfully increased the number of buyers each mount. Strategi promotional mix compiled by doing a few steps, include the identification of target markets, designing messages, media selection and determination of the promotion mix, so it will realize the goal of promotion, which is to create a positive image society and the buyer of the company, to attract buyers and retain existing customers, to realize the greatest possible sales transactions and to increase the optimal profit.